Analisis Perubahan Elemen Data Kependudukan Sesuai Dengan Permendagri Nomor 74 Tahun 2015 Pada Unit Pelaksana Teknis Dinas Kependudukan Dan Pencatatan Sipil Kecamatan Wanasaba - L Indra Buana Wirasandi, L Indra Buana Wirasandi (Fakultas Hukum Universitas Gunung Rinjani, 2024)
The purpose of this research is to find out the problem that will be researched in this thesis, namely how the Data Element Change Process and what the obstacls are faced in the Population Data Element Change Process in the Technical Implementation Unit of the Population and Civil Registration Service, Wanasaba District, East Lombok Regency and what are the Implications of the Population Data Element Change Process of Population Administration and other Cvil Registry. This type of research is normative-empirical in nature, where the implementation is carried out with case studies of the problems to be researched which are related to normative and empirical matters starting from positive legal provisions and then combined with events in society, while the approach method is used, namely the statutory approach, the conceptual approach and the case approach. Based on the research results, the process of changing population data elements is in accordance with the SOP (Standard Operating Procedure) at the Wanasaba District UPT. In the process of changing data elements at the Wanasaba District UPT, diplomas are often used as supporting documents, but changes to data elements can be made by court order. As an administrative requirement in accordance with Permendagri number 74 of 2015. How ever, the obstacles faced in changing data elements. Obstacles that often occur in changing data elements in the Wanasaba District UPT are often the lack of supporting documents submitted by the community as a condition for changing population data elements. Who want to change their E-KTP or Family Card but cannot show a diploma or other document as a conditionfor making the change due to various reasons (lost diploma).